Effectiveness of Organizing Musical Literacy Lessons in Interdisciplinary Communication - Khasanov Khalim Ravshanovich (Scientific Trends, 2025)
This article examines interdisciplinary connections in music lessons at school as an important element of the educational process. Emphasis is placed on the integration of music with other disciplines, such as literature, history, mathematics, geography and art. Examples of the use of an interdisciplinary approach that contributes to a deeper understanding of music and the development of students' creative abilities are given.
Keywords: Art, aesthetics, music, interdisciplinary relations, education, integration, personality, learning, culture.